Health Economic Aspects of Chimeric Antigen Receptor T-cell Therapies for Hematological Cancers: Present and Future. Issue 2 (28th February 2021) - Heine, Renaud; Thielen, Frederick W.; Koopmanschap, Marc; Kersten, Marie José; Einsele, Hermann; Jaeger, Ulrich; Sonneveld, Pieter; Sierra, Jorge; Smand, Carin; Uyl-de Groot, Carin A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Since 2018, 2 chimeric antigen receptor (CAR) T-cell therapies received approval from the European Medicine Agency, with list prices around 320 000 Euro (€) (EUR) per treatment. These high prices raise concerns for patient access and the sustainability of healthcare systems. We aimed to estimate the costs and budget impact associated with CAR T-cell therapies for current and future indications in hematological cancers from 2019 to 2029. We focused on the former France, Germany, Spain, Italy and the United Kingdom (EU-5) and the Netherlands. We conducted a review of list prices, health technology assessment reports, budget impact analysis dossiers, and published cost-effectiveness analyses. We forecasted the 10-year health expenditures on CAR T-cells for several hematological cancers in selected European Union countries. Nine cost-effectiveness studies were identified and list prices for CAR T-cell therapies ranged between 307 200 EUR and 350 000 EUR. Estimated additional costs for pre- and post-treatment were 50 359 EUR per patient, whereas the incremental costs of CAR T-cell therapy (when compared with care as usual) ranged between 276 086 EUR and 328 727 EUR. We estimated market entry of CAR T-cell therapies for chronic mantle cell lymphoma, follicular lymphoma, chronic lymphocytic leukemia, multiple myeloma, and acute myeloid leukemia in 2021, 2022, 2022, 2022, and 2025, respectively. Cumulative expenditure estimates for existing and future indications from 2019 to 2029 were on average 28.5 billion EUR, 32.8 billion EUR, and 28.9 billion EUR when considering CAR T-cell therapy costs only, CAR T-cell therapy costs including pre- and post-treatment, and incremental CAR T-cell therapy costs, respectively. CAR T-cell therapies seem to be promising treatment options for hematological cancers but the financial burden on healthcare systems in the former EU-5 and the Netherlands will contribute to a substantial rise in healthcare expenditure in the field of hematology.